The Effect of Store Atmosphere and Electronic Word of Mouth (E-WOM) On Customer Satisfaction at Sate Apaleh Geurugok Bireuen with Excellent Service as a Mediation Variable - Rahmah, Zulia; Setyaningrum, Retno Purwani (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Customer satisfaction is one of the keys to business success, including in the rapidly growing culinary sector. Sate Apaleh Geurugok Bireuen is a popular local culinary business, but it still faces challenges in maintaining customer satisfaction. The purpose of this study is to analyze The Influence of Store Atmosphere and Electronic Word of Mouth (eWOM) on Customer Satisfaction at Sate Apaleh Geurugok Bireuen with Excellent Service as a variable mediation. This study uses a quantitative method, sampling using the lemeshow formula, because the population size is unknown and a sample of 100 respondents was obtained. Data were collected through a questionnaire distributed using Google Forms. Data processing was carried out using Partial Least Squares (PLS) through the Structural Equation Model (SEM) technique with the help of the SmartPLS program version 4.1.1. The results of the analysis obtained are: Store atmosphere has a significant effect on customer satisfaction at Sate Apaleh Geurugok Bireuen. Electronic word of mouth does not have a significant effect on customer satisfaction on sate apaleh geurugok bireuen. Excellent service has a significant influence on customer satisfaction on sate apaleh geurugok bireuen. Store atmosphere has a significant influence on Excellent service on satay or Geurugok Bireuen. Electronic of mouth has a significant influence on Excellent service on satay or Geurugok Bireuen.Store atmosphere has a significant influence on customer satisfaction on sate apaleh geurugok bireuen with excellent service as a mediating variable. Electronic Word of Mouth has a significant influence on customer satisfaction on sate apaleh geurugok bireuen with excellent service as a mediating variable.